Método para harmonização de indicadores de performance entre diferentes domínios no contexto da indústria automotiva - Silva, Fernanda Antunes da (2018)
Given the current competition in the domestic and international markets, it is necessary for companies to monitor their practices and results in order to ensure competitiveness in the market. Organizations need to monitor processes through Key Performance Indicators (KPIs) in an integrated way, that is, different domains need to have activities and achievements aligned with each other. By using a harmonization approach both in the creation process and in monitoring the indicators, it is possible for companies to compete successfully. From a state-of-the-art research on this topic, it has been found that the integration between different domains within organizations is really a relevant subject and needs studies and suggestions to solve it. Considering this need, the present research project aimed to develop a method that allows harmonization of performance indicators within organizations, taking as context Purchasing and Logistics areas. By using this method, it will be possible for managers to make more assertive decisions, since these will be based on optimized scenarios. The ideal scenario to be signaled by the method will identify the gain for the organization as a whole, not just an isolated gain for a specific area. In this way, it is understood that, within the context of the automotive industry, the impacts caused by decisions taken within the supply chain will be minimized. As a methodological procedure, the research adopted the DSR (Design Science Research), and for the creation of this artifact (method), business processes modeling was performed following the BPMN (Business Process Model and Notation) standard. From this model, the main indicators and the way they are measured were identified. Finally, simulations were performed with the help of Bizagi software, seeking to verify potential opportunities to improve these indicators.